Harmful practices prevail despite legal knowledge: A mixed-method study on the paradox of child marriage in Bangladesh - Akter, Sayema; Williams, Chloe; Talukder, Animesh; Islam, Muhammed Nazmul; Escallon, Juanita Vasquez; Sultana, Tania; Kapil, Neha; Sarker, Malabika (Taylor & Francis, 2022)
This article was published in the Sexual and Reproductive Health Matters by Taylor and Francis [© 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group] and the definite version is available at: https://doi.org/10.1080/26410397.2021.1885790 The Journal's website is at: https://www.tandfonline.com/doi/full/10.1080/26410397.2021.1885790